Penyelarasan Strategi Bisnis dengan Strategi STI untuk Mencapai Tujuan Organisasi Menggunakan Ward and Peppard (Studi Kasus: SD XYZ) - Akbar, Ananda Azizul; Maulana, Yoppy Mirza; Wardhanie, Ayouvi Poerna (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2024)
SD XYZ is one of the oldest elementary schools in Gresik Regency which was established in 2010. The application of Information Systems and Technology at the school still does not support its organizational goals, where the Information Technology Systems used have not supported quality education and have not created active, creative and innovative learning. Therefore, this research makes a strategic planning of Information Technology Systems using the Ward and Peppard method or framework with stages such as external internal business analysis, and external internal Information Technology Systems analysis, then alignment is carried out using the Balanced Scorecard and also Critial Success Factors, based on the results of the alignment, it produces 15 application portfolios that are in accordance with the objectives of the organization, there are 2 key operational application portfolios for Quality A, 1 support application portfolio for Quality B, 2 support and 1 strategic for Quality C, 1 strategic, 3 high potential, 1 strategic and 2 support for Quality D, and 1 support for Quality E, and 2 application portfolios to support active, creative, and innovative learning.